2018
DOI: 10.1123/kr.2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

The Legacy and Influence of Catherine D. Ennis’s Value Orientations Research

Abstract: In this article, the authors examine work conducted on 6 value orientations in physical education pioneered by Dr. Catherine D. Ennis and her colleagues. After providing an overview they focus on areas and methods of VOI research, specifically descriptions and comparisons (gender, teachers’ experience, school level, nationality, location, level of training, race, and physical activity background), the influence of value orientations on pedagogy (content and instructional models), and interventions (curricula a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…disciplinary mastery and learning process) or affective (i.e. social responsibility, self-actualization, social reconstruction, and ecological integration) (Curtner-Smith et al, 2018). These earlier findings, however, may have been a function of an overreliance on a version of the value orientation inventory to categorize teachers’ value orientations, given that earlier qualitative work suggested that teachers favoring pairs of affective value orientations did so while also assuming that their job was to teach content (Chen and Ennis, 1996; Curtner-Smith et al, 2018; Ennis, 1992a, 1992b, 1994a, 1994b; Ennis et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…disciplinary mastery and learning process) or affective (i.e. social responsibility, self-actualization, social reconstruction, and ecological integration) (Curtner-Smith et al, 2018). These earlier findings, however, may have been a function of an overreliance on a version of the value orientation inventory to categorize teachers’ value orientations, given that earlier qualitative work suggested that teachers favoring pairs of affective value orientations did so while also assuming that their job was to teach content (Chen and Ennis, 1996; Curtner-Smith et al, 2018; Ennis, 1992a, 1992b, 1994a, 1994b; Ennis et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…social responsibility, self-actualization, social reconstruction, and ecological integration) (Curtner-Smith et al, 2018). These earlier findings, however, may have been a function of an overreliance on a version of the value orientation inventory to categorize teachers’ value orientations, given that earlier qualitative work suggested that teachers favoring pairs of affective value orientations did so while also assuming that their job was to teach content (Chen and Ennis, 1996; Curtner-Smith et al, 2018; Ennis, 1992a, 1992b, 1994a, 1994b; Ennis et al, 1992). In line with others (Gillespie, 2011; Sofo and Curtner-Smith, 2010; Timken and van der Mars, 2009), we believe that teachers’ value orientations are more accurately portrayed when qualitative as well as quantitative methods are employed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jewett, Bain, and Ennis [7] indicated that five value orientations influenced the teaching practice of physical education teachers, including disciplinary mastery, self-actualization, learning process, social reconstruction, and ecological integration. Later, in the early 1990s, social responsibility was added by Ennis and her research team to become the sixth value orientation [8]. Teachers who prioritize the social responsibility value orientation could focus on both individual development and sociocultural goals, and they believe that their main goal is to teach students personal and responsibility.…”
Section: Teaching Personal and Social Responsibility Modelmentioning
confidence: 99%